Routine measurement of health-related quality of life in assessing cost-effectiveness in secondary health care - Räsänen, Pirjo (Tutkimuksia / Sosiaali- ja terveysalan tutkimus- ja kehittämiskeskus, ISSN 1236-0732, 2007)
Abstract.
Keywords: Arthroplasty, Replacement, Hip; Arthroplasty, Replacement, Knee; Cataract Extraction; Cost-Benefit Analysis; Health Services Research; Hospital Costs; Quality of Life; Quality-Adjusted Life Years; Surveys and Questionnaires; Review Literature; Spinal Diseases : surgery; elämänlaatu; erikoissairaanhoito; terveys; kustannus-hyötyanalyysi; vaikuttavuus; livskvalitet; specialsjukvård; hälsa; kostnads-nyttoanalys; verkningsfullhet